THE HUMAN FACTOR: INVESTIGATING HOW NURSE CHARACTERISTICS SHAPE FALL PREVENTION TOOL USABILITY - Hiroko , Tanaka; Suzuki, Emi (Research Journal of Health, Medicine and Nursing, 2024)
Accidental falls represent a significant concern in Japanese hospitals, accounting for 19.3% of medical accidents. These falls result in not only physical injuries but also substantial social and economic consequences, including postfall syndrome and related medical costs. To mitigate this issue, comprehensive strategies encompassing staff and patient education, communication enhancements, and risk assessment are imperative. However, the current frequency and severity of fall-related incidents necessitate more comprehensive prevention measures. Falls are multifactorial incidents, influenced by a complex interplay of internal factors such as patients' physical and mental health and external factors including furniture and lighting. Given that falls can also occur in patients' daily lives, it is essential to consider not only medical staff vigilance but also the broader context of patient behavior and environment. Numerous fall risk assessment tools have been developed, with widely varying predictive accuracy. In particular, the St. Thomas's Risk Assessment Tool in Falling Elderly Patients (STRATIFY) has shown high sensitivity in acute hospital settings, while the Morse Fall Scale (MFS) demonstrated superior specificity. Moreover, the STRATIFY tool offers the advantage of quick completion, making it a valuable option for busy hospital environments.